2002
DOI: 10.1182/blood-2002-02-0621
|View full text |Cite
|
Sign up to set email alerts
|

High rate of clinical and molecular remissions in follicular lymphoma patients receiving high-dose sequential chemotherapy and autografting at diagnosis: a multicenter, prospective study by the Gruppo Italiano Trapianto Midollo Osseo (GITMO)

Abstract: Single-center experiences have shown that intensified treatments with autologous transplantation are a promising therapeutic strategy for patients with high-risk follicle-center lymphoma (FCL) at diagnosis, whereas data from prospective multicenter trials are still lacking. This paper describes the results of a prospective multicenter study of an intensified purging-free high-dose sequential (i-HDS) chemotherapy schedule with peripheral blood progenitor cell (PBPC) autografting. The main feature of this progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 53 publications
3
56
0
2
Order By: Relevance
“…If it would be possible to predict disease control after first-line therapy, these therapies could be selected for patients with a high likelihood of early relapse. With qualitative PCR, several studies were able to document a relationship between molecular response and time to relapse in patients treated with standard-dose chemotherapy [4,5,26], with high-dose chemotherapy [7,[27][28][29][30] and with rituximab-containing regimen [8,31,32]. Due to the low number of patients and the limited follow-up time of 6 months, we can only speculate on the role of molecular diagnostics for the prediction of relapsed disease.…”
Section: Discussionmentioning
confidence: 99%
“…If it would be possible to predict disease control after first-line therapy, these therapies could be selected for patients with a high likelihood of early relapse. With qualitative PCR, several studies were able to document a relationship between molecular response and time to relapse in patients treated with standard-dose chemotherapy [4,5,26], with high-dose chemotherapy [7,[27][28][29][30] and with rituximab-containing regimen [8,31,32]. Due to the low number of patients and the limited follow-up time of 6 months, we can only speculate on the role of molecular diagnostics for the prediction of relapsed disease.…”
Section: Discussionmentioning
confidence: 99%
“…50 susceptibility to infections, although most studies of rituximab (including our own) have not reported an increased incidence of opportunistic infections, 30,46,47 with the exception of some reports of increased cytomegalovirus and herpes zoster. 51,52 Hypogammaglobulinemia may be expected to be even more profound in contemporary patient cohorts who have received rituximab combination or maintenance as part of both their initial and relapse therapies. Both graft contamination and resistance to high-dose therapy likely contribute to FL relapse after HDT/auto-SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our results add to the growing body of literature, which suggests that molecular remission is an important predictor of long-term prognosis in FL. 32,33,51,59 We administered a single dose of rituximab to patients before stem cell collection as an in vivo purge. Belhadj et al 28 and Arcaini et al 29 used a similar strategy and achieved PCR-negative stem cell collections in 9 of 11, and 9 of 9 patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Por ello, se está realizando un gran esfuerzo con el fin de desarrollar técnicas lo suficientemente sensibles como para detectar la presencia de estas células que dan lugar a la denominada enfermedad mínima residual (EMR) 12 . La presencia de la translocación t (14;18) no posee valor pronóstico por sí misma pero hay estudios que han demostrado que la localización del reordenamiento bcl-2-JH puede correlacionarse con el desarrollo de la enfermedad 13,14 . Estos reordenamientos pueden ser analizados mediante técnicas de biología molecular, como la reacción en cadena de la polimerasa (PCR), para el diagnóstico de la EMR.…”
Section: Características Morfológicas/ Fenotípicasunclassified